Impact of Service Quality and Application of Sharia Principles on Consumer Intention of Sharia Hotel - Kamal, Al Haq; Salam, Abdul; Sani, Ageng Asmara; Brojosetami, Prabumadya; Sudibyo, Tyagita Dianingtyas (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
This research aims to measure and analyze the influence of quality of service and the application of sharia principles to consumers at Syariah Hotel Limaran. The data used in this study is primary data. Although the method of data collection used is simple random sampling with a sample of 60 customers of Syariah Limaran hotel, this research also uses observation, questionnaires, and documentation. The data analysis techniques in this study are descriptive analysis tests, multiple linear regression tests, partial (t) tests, simultaneous tests (f), and determinant coefficients (r2). Results obtained based on t and f test results produce a significant value of 0.05. Then the R Square value of 0.461 indicates that an independent variable can affect dependent variables by 46.10%. While other variables outside this study explain the remaining 53.90%. The study concludes that the quality of service and the application of sharia principles affect consumers' intention in Sharia hotels.